Training in digital and data skills can bridge the gender divide in agriculture - Agaton, Celina; Sharma, Sheetal (CGIAR System Organization, 2022)
Data collection and analytics are key functions in modern development projects, but are often performed by contracted staff who may be unaware of the local context and take their skills and data access with them after the project ends. To address this issue, the CGIAR Digital Innovation Initiative has partnered with the Open Knowledge Kit (OK Kit), created to enable people from local communities, especially women, to use digital tools and techniques to support continuous and consistent data collection methods and create local data employment opportunities across the Sustainable Development Goals. The first training took place in September 2022 in Bali, Indonesia.